SAT0453 Clinical, Autoimmune and Psychiatric Parameters in Systemic Sclerosis and Rheumatoid Arthritis Patients: Correlations with Sleep Disturbances. (9th June 2015) - Bagnato, G.; Visalli, E.; Fiorenza, A.; Cordova, F.; Greco, D.; Monaco, C.; Roberts, W.N.; Bruno, A.; Zoccali, R.; Bagnato, G.
Abstract : Background: Sleep disturbance has been identified as an important contributor to poor quality of life in rheumatic disorders 1 . Mood disorders and pain perception are considered the main factors influencing sleep quality. Objectives: This study aims to test whether clinical, autoimmune and psychological factors are associated with sleep disturbance in systemic sclerosis (SSc) compared to rheumatoid arthritis (RA) patients and controls. Methods: 101 female subjects (SSc=33, RA=34, healthy controls=34) participated in this observational, cross-sectional, parallel group study. Subjects affected by secondary fibromyalgia were excluded. Sleep disturbances have been assessed through the Pittsburgh Sleep Quality Index (PSQI). Other assessments included the visual analog scale (VAS) for pain, the Beck Depression Inventory (BDI) and the state trait anxiety inventory (STAI) Y1 and Y2. Clinical parameters, such as the modified Rodnan skin score (mRSS) for SSc and disease activity score 28 (DAS28) for RA patients, therapeutic regimen and autoantibody positivity were collected. Results: A PSQI score ≥5, cut-off value for the definition of poor sleeper, was found in 94% SSc patients, in 68% RA patients and in 20% healthy controls. In SSc PSQI scores were significantly higher than RA (p<0.05) and controls (p<0.0001). A higher incidence of mild to moderate symptoms of depression was observed in SSc compared to RA patients (49% vs 32%), while no differences were found in anxiety assessment. BDI and STAI-Y1 and Y2 scores did not differ between SSc and RA patients. Linear regression analysis showed that there was a significant correlation between BDI scores and PSQI in SSc (p=0.001, r2=0.30) and RA (p=0.0005, r2=0.32). Both STAI scores correlated with PSQI in SSc (STAI-Y1: p=0.001, r2=0.29; STAI-Y2: p=0.0009, r2=0.30), while no significant associations were found in RA. VAS scores correlated with PSQI both in SSc (p=0.0008, r2=0.39) and in RA (p=0.022, r2=0.22). In SSc, PSQI was significantly associated with mRSS (p=0.04, r2=0.12). In RA patients, PSQI scores correlated with the DAS28 (p=0.0049, r2=0.25); RA patients with disease activity higher than moderate (DAS28 >3.2, n=19) had significantly higher PSQI scores (p=0.02) than those with lower than moderate (DAS28 <3.2, n=15). SSc patients anti-Scl70 and ANA positive (n=15) showed higher PSQI scores compared to those ANA positive only (n=9) (p<0.01). PSQI scores in RA patients did not differ when divided according to rheumatoid factor positivity and according to the following treatment groups: disease modifying antirheumatic drugs (DMARDs), biologic, DMARDs + biologic, whereas significantly higher PSQI scores were observed in RA patients under corticosteroid treatment (n=14) compared to those who were not (n=20) (p=0.03). SSc patients under treatment with immunosuppressors (n=12) had significantly lower PSQI scores compared to those not on immunosuppressive therapy (n=21) (p=0.02). Conclusions: The definition of specific pattern of patients with higher risk to develop sleep disturbances could allow the clinician to better approach patients and to treat potentially modifiable factors. References: Abad VC et al. Sleep and rheumatologic disorders. Sleep Med Rev 2008;12:21128 Disclosure of Interest: None declared